2017
DOI: 10.1007/s13224-017-1058-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of Aspirin in High Pulsatility Index of Uterine Artery: A Consort Study

Abstract: In patients with high mean pulsatility index of uterine arteries, low dose aspirin can be a useful intervention. Uterine artery Doppler is a simple and noninvasive test which can be used safely for the prediction of preeclampsia. Aspirin is safe, economical, and easily available commercially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Acetylsalicylic is an anti-inflammatory medication that could decrease resistance in the uteroplacental blood flow by inhibiting thromboxane-mediated vasoconstriction and permitting prostacyclin-mediated vasodilation. 17 18 Recently, The Combined Multimarker Screening and Randomized Patient Treatment with Aspirin for Evidence-Based Pre-eclampsia Prevention (ASPRE) trial reported that ASA at a dose of 150 mg per day, started between 11 and 14 weeks, reduces the incidence of preterm PE by 62% in patients with a high risk of developing PE, 19 but a meta-analysis aimed at assessing the impact of the start of ASA intake at the 2 nd trimester in women with abnormal UtA-PI showed no benefit regarding the reduction of PE, suggesting that its action is lost after week 16. 20 Currently, there are not enough data to explain how the mean UtA-PI behaves as the gestation progresses when women take ASA before 14 weeks and it has not been explored whether ASA could modify the 95 th percentile of mean UtA-PI when patients with high risk of PE at the 2 nd and 3 rd trimesters are followed-up.…”
Section: Introductionmentioning
confidence: 99%
“…Acetylsalicylic is an anti-inflammatory medication that could decrease resistance in the uteroplacental blood flow by inhibiting thromboxane-mediated vasoconstriction and permitting prostacyclin-mediated vasodilation. 17 18 Recently, The Combined Multimarker Screening and Randomized Patient Treatment with Aspirin for Evidence-Based Pre-eclampsia Prevention (ASPRE) trial reported that ASA at a dose of 150 mg per day, started between 11 and 14 weeks, reduces the incidence of preterm PE by 62% in patients with a high risk of developing PE, 19 but a meta-analysis aimed at assessing the impact of the start of ASA intake at the 2 nd trimester in women with abnormal UtA-PI showed no benefit regarding the reduction of PE, suggesting that its action is lost after week 16. 20 Currently, there are not enough data to explain how the mean UtA-PI behaves as the gestation progresses when women take ASA before 14 weeks and it has not been explored whether ASA could modify the 95 th percentile of mean UtA-PI when patients with high risk of PE at the 2 nd and 3 rd trimesters are followed-up.…”
Section: Introductionmentioning
confidence: 99%
“…The first wave of trophoblast migration occurs at 10 to 14 weeks; the second wave of trophoblast migration in the deep myometrium begins by 18 to 20 weeks and is completed only by 22 to 24 weeks. [24] Nonetheless, some studies have indicated that aspirin started in the late second and third trimester could also prevent eclampsia. [40,41] The American College of Obstetricians and Gynecologists recommends low-dose aspirin (81 mg/d) for prevention from 12 to 28 weeks of gestation until delivery.…”
Section: Discussionmentioning
confidence: 99%
“…[23] There is a positive association between maternal BMI and fetal weight. [24] Obesity might increase the levels of inflammatory markers. [25] Chronic chorioamnionitis has been associated with preterm stillbirth potentially caused by maternal anti-fetal rejection, which may explain approximately 10% of the effect of obesity on the risk of stillbirth.…”
Section: Risk Factors For Stillbirth In Dipmentioning
confidence: 99%